Adapted silver impregnation protocol for the detection of Merkel cells in fish skin embedded in plastic historesins - Conrado, André Luiz Veiga; Silva, José Roberto Machado Cunha da (Brazilian Journal of Science, 2026)
Merkel cells are detected using silver impregnation in skin samples embedded in paraplast. Here, we describe an adapted protocol for detecting Merkel cells in Amur carp (Cyprinus rubrofuscus) skin samples embedded in historesin. Incubated slides in Grimelius silver impregnation solution at 60 ºC for five hours resulted in positive Merkel cells scattered among skin cell layers composed of Malpighian, goblet, and club cells. Thus, Merkel cells can be explored in samples embedded in historesins using adapted protocols for paraplast ones.